THE EFFECTS OF PANORAMIC RADIOGRAPHY ON GINGIVAL CREVICULAR FLUID VOLUME IN GINGIVITIS - Rini Rahmiyati; Didit Aspriyanto; Beta Widya Oktiani (FKG Unlam, 2021)
Background: Gingival crevicular fluid (GCF) is a biological fluid derived from the gingival sulcus and can be elevated in the inflammatory state of periodontal tissue, such as gingivitis. In previous studies, the number of GCF could also increase after panoramic radiographic exposure. Increase in GCF due to panoramic radiography is a sign of cell damage. Objective: To analyze the effects of panoramic radiography on the volume of GCF in wistar rats with gingivitis. Method: This type of research was true experimental with post test only and control group design. The sampling technique used was simple random sampling. A total of 25 wistar rats were classified into two control groups without exposure (state without gingivitis and gingivitis) and three groups treatment of exposure (state of gingivitis with 1 time, 2 times, and 3 times the exposure). GCF sampling using filter paper was carried out 10 minutes after panoramic radiographic exposure. The filter paper was stained by 2% ninhydrin solution, after that the GCF volume was calculated. Results: There was a significant difference in the number of GCF (p<0.05) in the group without gingivitis and exposure compared to all other groups, the gingivitis group without exposure compared to the gingivitis group with 3 times exposure, and the gingivitis group with 1 time exposure compared to the gingivitis group 3 times with exposure. Conclusion: Panoramic radiography can cause an increase in the volume of GCF in wistar rats with gingivitis. Keywords: GCF, gingivitis, panoramic radiography